2022
DOI: 10.31605/saintifik.v8i1.357
|View full text |Cite
|
Sign up to set email alerts
|

Praktik-Praktik Pembelajaran Daring sebagai Bentuk Inovasi Dosen Universitas Sulawesi Barat

Abstract: Pembelajaran daring merupakan strategi yang diambil oleh pemerintah sebagai salah satu metode agar pendidikan dapat tetap berjalan meskipun dalam situasi pandemi. Baik dosen maupun mahasiswa dipaksa agar terbiasa menerapkan pola pembelajaran daring. Banyaknya permasalahan yang mencuat selama awal penerapan pembelajaran daring merupakan tantangan bagi dosen maupun mahasiswa dalam menjalankan tugasnya masing-masing, sehingga tujuan pembelajaran dapat tercapai dan kualitas output yang diharapkan tetap terjaga. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Moreover, in a critical thinking test, pre-service Biology teachers performed poorly by achieving an average score of 61.39 with the lowest score (27.14) observed in the "drawing conclusions" indicator and the highest score (79.39) found in the "evaluating arguments" indicator [10]. Several other related studies suggested that students' critical thinking in universities needs to be developed [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a critical thinking test, pre-service Biology teachers performed poorly by achieving an average score of 61.39 with the lowest score (27.14) observed in the "drawing conclusions" indicator and the highest score (79.39) found in the "evaluating arguments" indicator [10]. Several other related studies suggested that students' critical thinking in universities needs to be developed [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%